New Religious Movement: Conservation of Cultural Belief Teachings in Lembang District, West Bandung Regency - Wahyudin, Yudi; Kahmad, Dadang; Syukur, Abdul (Hanifiya: Jurnal Studi Agama-Agama, 2025)
This study explores the persistence of Budi Daya Faith as a form of New Religious Movement (NRM) in Lembang Subdistrict, West Bandung Regency, Indonesia. Using a qualitative ethnographic approach through participatory observation, in-depth interviews, and documentation over two years, the research examines how followers of Budi Daya maintain a coherent spiritual system across five dimensions of religiosity: belief in Hyang Tunggal as the Supreme Divine, symbolic ritual practices, oral transmission of sacred knowledge, personal spiritual experience, and ethical consequences in daily life. Despite facing marginalization and state regulatory limitations, the community survives by adapting its doctrine, preserving cultural expressions, and cultivating harmony with nature and society. This study concludes that Budi Daya Faith is not merely an ancestral tradition but a legitimate form of religious identity. It offers valuable insights into religious pluralism, the dynamics of indigenous belief systems, and the urgency of recognizing spiritual expressions outside of state-defined religions.